A prospective study contrasting the psychiatric outcome in drug‐resistant epilepsy between patients who underwent surgery and a control group. (26th August 2016) - Ramos‐Perdigués, Sònia; Baillés, Eva; Mané, Anna; Carreño, Mar; Donaire, Antonio; Rumia, Jordi; Bargalló, Nuria; Boget, Teresa; Setoain, Xavier; Valdes, Manuel; Pintor, Luís
Summary: Objective: Psychiatric morbidity in drug‐resistant epilepsy is frequent and has a negative influence on quality of life. Surgery is proven to be the best therapeutic alternative for treating seizures. However, it is inconclusive with the current evidence whether surgery, per se, is a risk factor or promotes amelioration of psychiatric disorders. Until now, most studies have been cross‐sectional with small or heterogeneous groups. In addition, the few prospective studies did not have an identical control group. The present study aims to clarify the role of surgery in psychopathologic alterations. Methods: We analyzed, through a prospective case‐control study, the psychopathologic outcomes of patients with drug‐resistant epilepsy, comparing those who underwent surgery and those who continued with pharmacologic treatment due to not being suitable for surgery. The assessments were performed during presurgical evaluation and 6 months after surgery. We studied psychiatric changes for each group, compared differences between groups, and also analyzed de novo and remission cases. Finally, we determined associated factors for postsurgical psychiatric disturbances. Results: The surgical group experienced a significant decrease in psychopathologic alterations in comparison with the control group. In addition, distress perception of surgical patients also improved, whereas it did not decrease in the control group. Patients who underwent surgery presented a decrease in depressive and anxiety symptoms, whereas the nonsurgical group increased its anxiety levels. De novo disturbances that appeared after surgery were less frequent than in nonsurgical patients. We observed significant favorable outcomes considering de novo versus remission cases for anxiety, depression, and total symptoms only in the surgical group. The two main predictors for psychiatric disorders after surgery were presurgical psychiatric functioning and surgery. Significance: Provides evidence that surgery improves psychiatric functioning in drug‐resistant epilepsy through a prospective controlled study.